Penerapan Model Waterfall Dan Blackbox Testing Dalam Pembuatan Sistem Informasi E-Aset Desa Berbasis Web - saifudin; saifudin, saifudin (Informatics and Computer Engineering Journal, 2021)
Abstract - At this time the management of assets owned by the village still uses a manual system with the method of writing in the notebook and want to be recaped to make a report. Technological advances demand to grow out of manual ordinances leading to the digital age. Utilization of technology has been tested to support the performance of information processing that takes a long time so lightning let alone better with electronic media. The use of electronic media makes it easy to access anything easily and lightning and carry out inputs let alone edit information directly. Pc for example, a very helpful media once in the process of managing information so data. This research aims to design and build a data system for village asset management. The state of the village office which is categorized as small makes management complicated with various assets. With frequent repetition of information because the village features do not remember while carrying out recording or checking information that is still written manually. Running out of objects and errors while recording asset returns makes the problem more complicated. The use of waterfall procedures can make it easier to create an e-asset data system because the stages of development have been clearly established and in the final stage of testing with blackbox testing to see there are errors that exist in the system.